2018
DOI: 10.3847/1538-4357/aad6e0
|View full text |Cite
|
Sign up to set email alerts
|

Habitability of Exoplanet Waterworlds

Abstract: Many habitable zone (HZ) exoplanets are expected to form with water mass fractions higher than that of the Earth. For rocky exoplanets with 10-1000× Earth's H 2 O but without H 2 , we model the multi-Gyr evolution of ocean temperature and chemistry, taking into account C partitioning, high-pressure ice phases, and atmosphere-lithosphere exchange. Within our model, for Sun-like stars, we find that:(1) the duration of habitable surface water is strongly affected by ocean chemistry; (2) possible ocean pH spans a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 286 publications
(316 reference statements)
3
92
0
Order By: Relevance
“…This is especially true for water worlds like the ones proposed in the TRAPPIST-1 system (Grimm et al, 2018;Unterborn et al, 2018). The self-consistent thermodynamic properties for water and its ices provided by SeaFreeze can be used to accurately study the interior structure and evolution of watery exoplanets (Noack et al, 2016), computing of radius-mass curves (Sotin & Grasset, 2007;Unterborn et al, 2018), as well as studying their habitability and the effects of possible snow-ball regime on ocean words (Kite & Ford, 2018;Ramirez & Levi, 2018). It should be noted that these world's hydrospheres could be significantly thicker than those of large icy moons, resulting in possibly ice VII and ice X being present as well.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for water worlds like the ones proposed in the TRAPPIST-1 system (Grimm et al, 2018;Unterborn et al, 2018). The self-consistent thermodynamic properties for water and its ices provided by SeaFreeze can be used to accurately study the interior structure and evolution of watery exoplanets (Noack et al, 2016), computing of radius-mass curves (Sotin & Grasset, 2007;Unterborn et al, 2018), as well as studying their habitability and the effects of possible snow-ball regime on ocean words (Kite & Ford, 2018;Ramirez & Levi, 2018). It should be noted that these world's hydrospheres could be significantly thicker than those of large icy moons, resulting in possibly ice VII and ice X being present as well.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…As a common molecular species in our cosmic neighborhood (Hanslmeier, ), water ice polymorphs at high pressures in planetary interiors could be the most abundant “mineral group” in the Universe. A focus on potentially habitable hydrospheres of icy moons, small bodies such as Pluto and Ceres, and ocean exoplanets (Sotin & Tobie, ; S. Vance & Brown, ; B Journaux et al, ; Baptiste Journaux et al, ; Noack et al, ; Kite & Ford, ; Unterborn et al, ; Hendrix et al, ) motivates an interest in thermodynamic properties of water and ices in the <200 MPa range. For example, the presence of an insulating layer of high‐pressure ice between the deep ocean and the underlying silicates on large water‐rich planetary bodies has been identified as a potential bottleneck for habitability, as it could limit nutrient transport (Léger et al, ; Noack et al, ; Baptiste Journaux et al, ; Kite & Ford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Even the direction of the changes is unclear. In contrast to pelagic planets, the outgassing of CO 2 from silicate melts very likely would be suppressed at pressures > 100-200 MPa due to the presence of a high-pressure ice layer (Kite & Ford 2018). This would effectively reduce or eliminate the influx of CO 2 to the atmosphere, leading to a colder planet, and one on which the carbonate-silicate cycle is no longer self-regulated (Cowan & Abbot 2014).…”
Section: Limitations To Oxygen Productionmentioning
confidence: 99%
“…The ocean mass of 200 M oc,⊕ that we adopt here corresponds to the ocean layer of ∼350 km for T s = 300 K. We do not consider ocean planets with more massive oceans because such planets are expected to have no geochemical cycle. For planetary climates with no geochemical cycle, see Kitzmann et al (2015) and Kite & Ford (2018). Note that we assume a spherically symmetric structure in the internal structure modeling, while we consider the presence of the sorbet and HP ice regions in the deep ocean in the seafloor environment modeling.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…This suggests that such a climate system is an unstable one with a positive feedback cycle. Kite & Ford (2018) considered supply of cations to the ocean, which strongly affects ocean chemistry, in the initial, hot stage after solidification of the magma ocean. They showed that large cation concentration enhances the positive feedback and leads to destabilizing planetary climate into hot one for a large CO 2 inventory (∼ 100 bars) in the atmosphere-ocean system even for stellar insolation comparable to the present Earth.…”
Section: Introductionmentioning
confidence: 99%